Polymer Gels Synthesis and Characterization - Thakur, Vijay Kumar; Thakur, Manju Kumari; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book addresses a range of synthesis and characterization techniques that are critical for tailoring and broadening the various aspects of polymer gels, as well as the numerous advantages that polymer gel-based materials offer. It presents a comprehensive collection of chapters on the recent advances and developments in the science and fundamentals of both synthetic and natural polymer-based gels. Topics covered include: synthesis and structure of physically/chemically cross-linked polymer-gels/polymeric nanogels; gel formation through non-covalent cross-linking; molecular design and characterization; polysaccharide-based polymer gels: synthesis, characterization, and properties; modified polysaccharide gels: silica-based polymeric gels as platforms for the delivery of pharmaceuticals; gel-based approaches in genomic and proteomic sciences; emulgels in drug delivery; and organogels. The book provides a cutting-edge resource for researchers and scientists working in various fields involving polymers, biomaterials, bio-nanotechnology and functional materials.
Structure and Physico-Mechanical Properties of Physically Cross-Linked Polymer-Gels -- Polymer Gels: Molecular Design and Properties -- Polymer Gel and Immunity in Regenerative Medicine -- Polysaccharide-Based Polymer Gels: Synthesis, Characterization, And Properties -- Modified Polysaccharide Gels: Characterization And Pharmaceutical Applications -- Silica-Based Polymeric Gels As Platforms For Delivery Of Pharmaceutics -- Polymeric Nanogel: A Flexible Nanocarrier For Drug Delivery -- Gel-Based Approaches In Genomic And Proteomic Sciences -- Emulgels In Drug Delivery: Synthesis And Characterization -- Gel Formation Through Non-Covalent Cross-Linking From Amylose Formed By Enzymatic Polymerization -- Organogels: Preparation And Properties For Different Industries -- Preparation And Characterization Of The Ionic Gels Derived From Cellulose -- Smart Polymer Gels -- Polymer Gels Of Biological Origin And Their Role In Nature, Biomedicine And Biotechnology -- Enhancing An Intrinsic Path Of Axon Regeneration By Polymer Gels -- Neuro-Evolutive Techniques Applied For Modeling Processes Involving Polymer Gels -- Polymer Gels In Vaginal Drug Delivery Systems: Synthesis And Properties -- Polysaccharide Based Gels For Drug Delivery.
Keywords: Polymers; Biomedical engineering; Pharmaceutical chemistry; Biomaterials; Polymers; Biomedical Engineering and Bioengineering; Pharmaceutics; Biomaterials